Beneficial changes in food consumption and nutrient intake after 10 years of follow-up in a Mediterranean cohort: the SUN project - de la Fuente-Arrillaga, Carmen (BMC Public Health, 2016)
BACKGROUND: The assessment of changes in dietary habits provides interesting information on whether or not the observed trends are in line with accepted nutritional guidelines. The objective was to evaluate within-subject longitudinal changes in food consumption and nutrient intake and in a 10-year follow-up study. METHODS: The SUN (Seguimiento Universidad de Navarra) project is a prospective Spanish cohort study. Diet was assessed using a 136-item food-frequency questionnaire (FFQ), previously validated in Spain. The participants were 3036 university graduates (55.8 % women) of Spain and the main outcome measures the changes in dietary quality and in food consumption and nutrient intake. Paired t-tests and conditional logistic regression models were used to evaluate within-subject longitudinal dietary changes and the risk of inadequacy respectively, after 10 years of follow-up. RESULTS: During follow-up, participants showed a relevant and significant increase (p < 0.001) in the consumption of fruits (7.4 %), vegetables (8.6 %), low-fat dairy products (35.2 %), lean meat (12.4 %), fish (2.9 %), whole grains (53.2 %), nuts (52.4 %) and a significant decrease in legumes (−7.4 %), whole-fat dairy products (−44.2 %), red meat (−17.6 %), sugar-sweetened beverages (−58.7 %) and wine (−11.9 %). With respect to nutrients, we found a higher proportion of carbohydrates (3.6 %) and fiber (7.4 %) and a decrease in total energy intake (2.7 %), total fat (−4.5 %), SFA (−9.4 %), MUFA (−4.9 %), PUFA (−12.7 %), w-3 and w-6 fatty acids (−9.1 and −20.5 % respectively) and cholesterol (−9.6 %). CONCLUSIONS: In this Mediterranean cohort study, mainly beneficial changes in the consumption of most foods and macronutrients were observed after 10 years of follow-up.